ANALYSIS AND MODELLING OF POLLUTANTS MIGRATION (CS-137) IN CASCADE OF DIDORIVSKY PONDS IN THE HOLOSIIVSKYI PARK - Kravets, Maria; Kutlakhmedov, Yuri; Tuleninov, Konstantyn; Salivon, Anastasiya (Proceedings of National Aviation University, 2015)
The basic model of radionuclide content of Cs-137 in the cascade Didorivsky ponds was constructed. The cascade monitoring data were obtained. Base model extrapolation was made up on the base of the observed data and accurate model of the cascade was obtained. Model extrapolation resulted in conclusions concerning accumulation of Cs-137 radionuclide in the cascade of Didorivsky ponds for 50 years.